Facing up to the facts: What causes economic perceptions? - Hobolt, Sara; Tilley, James; de Vries, Catherine (Elsevier, 2018)
The link between individual perceptions of the economy and vote choice is fundamental to electoral accountability. Yet, while it is well-established that economic perceptions are correlated with voting behaviour, it is unclear whether these perceptions are rooted in the real economy or whether they simply reflect voters’ partisan biases. This article uses time-series data, survey data and unique experimental evidence to shed new light on how British voters update their economic perceptions in response to economic change. Our findings demonstrate that while partisanship influences levels of economic optimism, people respond to information about real economic changes by adjusting their economic perceptions.
Keywords: 59 Ciencia Política; ODS 10 - Reducción de las desigualdades; ODS 16 - Paz, justicia e instituciones sólidas